Challenges facing small and medium enterprises in the low cost housing sector in Limpopo - Sekoati, Seaparo Charles. (University of Limpopo, 2010)
Refer to document
Thesis ( M.Dev.) -- University of Limpopo, 2010
Keywords: Small medium interprices; Business enterprises; Construction industry - South Africa; Economic development - South Africa - Limpopo